2016
DOI: 10.4236/ajac.2016.77054
|View full text |Cite
|
Sign up to set email alerts
|

Express Screening of Biological Objects Using Multisensor Stripping Voltamperometry with Pattern Recognition

Abstract: Express diagnostics of biological objects is necessary for operational preliminary assessment of the condition of the patient. A method of recognition of differences between the norm and pathology is based on analysis of multidimensional patterns of the voltamperogram electrochemical test systems in Electronic formats "language", "electronic nose". The basis of such systems is the use of a set (matrix) sensor with completely different characteristics. A. N. Frumkin Institute of Physical Chemistry and Electroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Electrochemical inversion methods cannot, in principle, be used for continuous determinations because of the need for sequential stages of accumulation and dissolution; however, they are suitable for performing automatic serial analyzes during certain time intervals if suitable programming equipment is available. , Examples are software-controlled devices that use a stationary mercury drip electrode and a rotating mercury film electrode. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical inversion methods cannot, in principle, be used for continuous determinations because of the need for sequential stages of accumulation and dissolution; however, they are suitable for performing automatic serial analyzes during certain time intervals if suitable programming equipment is available. , Examples are software-controlled devices that use a stationary mercury drip electrode and a rotating mercury film electrode. …”
Section: Methodsmentioning
confidence: 99%
“…Further studies have shown the working capacity and effectiveness of the method, in particular, when analyzing a number of ophthalmic drugs: Visomitin and Lanosterol . An increase in the strength of the complex present in the background increases the height of the peak of the metal dissolution current and, accordingly, decreases its width. Assessment of the dynamics of changes in their concentration in the lacrimal fluid over time must determine the effective dosage of newly developed analgesic ophthalmic drugs. This study aimed to study the behavioral pharmacokinetics in the lacrimal fluid of an opioid drug, sevoflurane, in pediatric ophthalmology using multisensory stripping voltammetry in patients during strabismus correction surgery.…”
Section: Methodsmentioning
confidence: 99%
“…The analyzer embodies a new approach using a solution containing various metal ions as an electrochemical testsystem, the ions being able interact with organic substances to form complex compounds [21][22][23][24][25][26][27][28][29][30][31]. All known E-tongue devices use a set of electrodes as sensors, therefore the reproducibility of characteristics of the multi-sensor systems is problematic, which affects the reliability and pattern recognition in a negative way.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements are performed on a single indicator electrode, which has a significant advantage compared to multi-sensor methods using a range of electrodes. This method allows the identification of organic substances using a preliminary database.The effectiveness of this method has been shown for several ophthalmic medications: Visomitin, Betoptic, and Lanomax [27][28][29][30]. The concentration of Visomitin in the lacrimal fluid was measured based on a calibration relationship.…”
Section: Introductionmentioning
confidence: 99%